Destination Therapy with Left Ventricular Assist Devices in Non-transplant Centres: The Time is Right. Issue 1 (2020) - Bayes-Genis, Antoni; García-García, Cosme; Muñoz-Guijosa, Christian; Codina, Pau; Santiago-Vacas, Evelyn; Montero, Julio Núñez Santiago; Lupón, Josep
No abstract available